FACILITIES UTILIZATION IN LAMPULO FISHERIES PORT, DISTRICT OF KUTA ALAM, BANDA ACEH CITY, PROVINCE NANGGROE ACEH DARUSSALAM - Zulmaidah '; Jonny Zain; Ronald Mangasi Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on April 2015 in Lampulo fisheries port, Gampong Lampulo district of Kuta Alam Banda Aceh Propince Nanggroe Aceh Darussalam. The goal is to identify facilities type and its conditions as well as its level of utilization. This research use survey methods, facilities of lampulo port consists of primary facilities, functional facilities and supporting facilities, but some facilities in bad condition and not to be used and some is still in progress, some other facilities is used but not fort its function it is caused some activities is moved to new port them the facilities is no more utilized. Utilization level <25 % indicated for port basin (8,36 %), level of utilization for <50 % is for depth of port basin (45,20 %) facilities for level of utilization for >75 % is for fish auction place (79,58 %), meanwhile for level of utilization for 100 % is for unloading dock (145,36 %), loading dock (174,98 %), fuel oil tank (129,27 %), ice company, and a fresh water tank. The things must be done for over optimal utilization level is addition of area and capacity meanwhile for facilities under optimal must been increase its utilization level.Keyword: PP Lampulo , the facility needs analysis , utilization of facilities